Acute toxicity of commercial wildfire retardants to two daphniid species (Ceriodaphnia dubia and Daphnia magna) - Brito, Darlan Quinta (2024)
In the face of global climate change, there has been an increase in wildfires around the world, highlighting the need for improved firefighting techniques, such as the use of fire retardants (FRs). These products can enter aquatic systems directly or through runoff, posing potential risks to aquatic biota. In this study, the acute toxicity (24-h/48-h EC50) of three distinct FRs (N-Borate, N-Phosphate+, and N-Phosphate−) was assessed on the immobility of freshwater microcrustaceans Ceriodaphnia dubia and Daphnia magna. The toxicity of the FRs varied up to two orders of magnitude, all of which presented risks to cladocerans even at dilutions much below those recommended by their manufacturers. Among the tested FRs, N-Phosphate− emerged as the most harmful to both species. Specifically, for C. dubia, the 24 h EC50 was 0.005% and the 48 h EC50 was 0.0019%, while for D. magna, 24 h EC50 was 0.003% and the 48 h EC50 was 0.0023%. With the increasing use of FRs for wildfire control, our study highlights the toxicity of newly formulated FRs to daphniid species and emphasizes the need for further evidence-based evaluations of their effects on freshwater ecosystems, which is crucial for choosing FRs that pose the lowest hazard to zooplankton communities.